High-performance silicon-carbon negative electrode material and preparation method and application thereof
The preparation of high-performance silicon-carbon negative electrode materials through electrospinning process solves the problems of volume expansion and low conductivity of silicon-carbon materials in lithium-ion batteries, significantly improves the battery capacity and cycle stability, and has environmental protection and cost-effective advantages.
Patent Information
- Application Number
- CN202510051167.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-08
AI Technical Summary
In the prior art, the silicon carbon anode material expands in volume during the complete lithiation of lithium-ion batteries and has a low conductivity, which affects the cyclic stability and capacity retention rate of the battery.
By mixing nanosilicon, polymer and solvent to form a spinning raw liquid, an electrospinning process is used to prepare a polymer fiber membrane dispersed with nanosilicon, and high-temperature carbon anode material is prepared under a protective atmosphere.
It significantly improves the overall performance of lithium-ion batteries, improves the battery capacity and circulation life, and reduces the volume expansion problem, and has environmentally friendly and cost-effective advantages.
Smart Images

Figure CN119777069A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium-ion battery negative electrode materials, and in particular to a high-performance silicon-carbon negative electrode material and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries, the primary power source for portable electronic devices, electric vehicles, and power tools, face the challenge of meeting market demand for higher capacities due to the low capacity of existing carbon-based anode materials. To overcome this bottleneck, researchers are actively exploring new carbon materials and high-capacity non-carbon materials such as tin, silicon, and metal oxides to improve battery performance.
[0003] Silicon stands out as a highly promising anode material, with a theoretical capacity of approximately 4200 mAh / g, far exceeding the 370 mAh / g of commercial graphite anodes. However, silicon undergoes approximately 400% volume expansion during full lithiation, which not only causes severe structural damage and loss of electrical contact, affecting cycling stability, but also its inherent low electrical conductivity hinders its practical application.
[0004] To overcome the above difficulties, the methods currently used are: shortening the lithium ion diffusion path through nano-silicon materials, thereby reducing the stress caused by volume changes; compounding silicon with conductive materials, such as constructing a uniformly dispersed doping structure, carbon coating or core-shell structure, to enhance conductivity and adapt to silicon's volume changes. In particular, silicon / carbon composite materials have become one of the effective ways to solve these problems due to their excellent conductivity. Common preparation methods for silicon-carbon materials, such as mechanical ball milling, may introduce impurities, long-term ball milling will destroy the crystal structure, and the material uniformity is difficult to accurately control; chemical vapor deposition requires high temperature, complex equipment and special reaction gases, which is costly, complex, and has low yields, making it unfavorable for large-scale production; the sol-gel method involves multiple complex chemical reactions, strict reaction conditions, and a long preparation cycle. The gel is prone to shrinkage and cracking when drying, affecting performance. Currently, electrospinning technology has significant advantages in preparing silicon-carbon anodes. These advantages are primarily manifested in the following aspects: first, it is simple to operate and readily scalable, and it can precisely create one-dimensional silicon / carbon nanofiber structures that combine the high capacity of silicon with the good conductivity of carbon. Second, this structure allows silicon to be evenly dispersed within the carbon matrix, inhibiting silicon volume expansion and improving structural stability and interfacial compatibility. However, the current application of electrospinning technology to prepare silicon-carbon anode materials still presents the problem of silicon volume expansion during complete lithiation and low conductivity. Summary of the Invention
[0005] The purpose of the present invention is to provide a method for preparing a high-performance silicon-carbon negative electrode material, which is used to solve the problems of volume expansion and low conductivity of silicon during complete lithiation in the preparation method of the prior art.
[0006] The present invention also provides a high-performance silicon-carbon negative electrode material to solve the problem of poor electrical conductivity of silicon-carbon negative electrode materials in the prior art.
[0007] The present invention also provides a negative electrode plate to solve the problem of poor electrochemical characteristics of negative electrode plates in the prior art.
[0008] In order to solve the above problems, the present invention proposes a method for preparing a high-performance silicon-carbon negative electrode material, and the technical solution adopted is: A method for preparing a high-performance silicon-carbon negative electrode material comprises the following steps: mixing nano-silicon, a polymer and a solvent to form a spinning solution, performing an electrostatic spinning process to obtain a polymer fiber membrane dispersed with nano-silicon, and performing high-temperature carbonization under a protective atmosphere to obtain a silicon-carbon negative electrode material.
[0009] The beneficial effects of the present invention are: The present invention enhances the electrical conductivity and alleviates the volume change of silicon by combining nano-silicon with polymers and solvents through an electrospinning process and high-temperature carbonization. In the present invention, the electrospinning process plays a very important role in the design of silicon / carbon nanofiber structures. Its main function is to promote ion conduction during energy storage. The preparation method of this high-performance silicon-carbon negative electrode material has the advantages of being fast, simple, environmentally friendly and low-cost. The material synthesis process is simple, which improves production efficiency. The present application significantly improves the overall performance of lithium-ion batteries by optimizing the diffusion path of lithium ions. Its application in lithium-ion batteries can significantly increase the capacity of the battery and extend its cycle life; and it can exhibit excellent performance under various charge and discharge environments. In addition, the negative electrode material prepared by the electrospinning process makes the corresponding lithium-ion battery also have excellent safety and reliability, showing a wide range of application prospects. The silicon-carbon negative electrode material prepared by the preparation method of the high-performance silicon-carbon negative electrode material of the present invention is used as the negative electrode of the lithium-ion battery, while effectively solving the volume expansion problem of the silicon negative electrode material and achieving dual optimization of environmental protection and cost-effectiveness.
[0010] In order to further enhance the electrical conductivity and alleviate the volume change of silicon, preferably, the mass ratio of the nano-silicon to the polymer is (0.01-3):1; and the particle size of the nano-silicon is 10-800 nm.
[0011] In order to further reduce volume expansion and increase the dispersibility of the raw materials, preferably, the polymer is one or more of polyethylene oxide, polycaprolactone, polyvinyl alcohol, polyvinyl pyrrolidone, polyvinylidene fluoride, polyacrylonitrile, polylactic acid, polyether sulfone, polyurethane, polystyrene, and polyamide.
[0012] In order to fully dissolve the polymer, preferably, the solvent is one or more of deionized water, ethanol, N,N-dimethylformamide, N,N-dimethylacetamide, chloroform, tetrahydrofuran, hexafluoroisopropanol, dichloromethane, acetone, and formic acid.
[0013] In order to improve the cycle stability and capacity retention of the lithium-ion battery, preferably, the temperature of the high-temperature carbonization is 300-700° C. and the time is 1-6 hours.
[0014] In order to further improve the solubility of the polymer, preferably, the mass ratio of the polymer to the solvent is (1:8) to (1:9).
[0015] In order to further promote ion conduction during the energy storage process, preferably, in the electrospinning process, the spinning solution enters from a needle; wherein the propulsion rate of the spinning solution is 0.01~0.8mL / h, the inner diameter of the needle is 0.11~3.10mm, the outer diameter of the needle is 0.25~3.50mm, and the roller receiving distance is 10~20cm.
[0016] In order to improve the stability of the spinning process and the stability of the product morphology, preferably, in the electrospinning process, the voltage is 12~28kV, the temperature is 15~25℃, and the humidity is 20~50%.
[0017] The present invention also proposes a high-performance silicon-carbon negative electrode material, the technical solution adopted is: A high-performance silicon-carbon negative electrode material is prepared by the above-mentioned method for preparing the high-performance silicon-carbon negative electrode material.
[0018] The beneficial effects of the present invention are: the high-performance silicon-carbon negative electrode material of the present invention has high conductivity and reduces the volume expansion of silicon during the complete lithiation process.
[0019] The present invention also proposes a negative electrode plate, the technical solution adopted is: A negative electrode plate comprises the high-performance silicon-carbon negative electrode material prepared by the above-mentioned preparation method of the high-performance silicon-carbon negative electrode material or the above-mentioned high-performance silicon-carbon negative electrode material.
[0020] The beneficial effects of the present invention are: the negative electrode plate exhibits excellent electrochemical properties, can significantly improve the capacity of the battery and extend its cycle life.
[0021] The present invention also proposes a lithium-ion battery, the technical solution adopted is: A lithium-ion battery comprises the above-mentioned negative electrode plate.
[0022] The invention has the following beneficial effects: the lithium-ion battery has high capacity and excellent stability, and can demonstrate excellent performance under various charge and discharge conditions. In addition, by using a negative electrode material produced by an electrospinning process, the battery also has excellent safety and reliability. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a SEM image of a polymer fiber membrane dispersed with nano-silicon prepared in Example 1 of the method for preparing a high-performance silicon-carbon negative electrode material of the present invention; Figure 2 This is the XRD pattern of the high-performance silicon-carbon negative electrode material prepared in Example 2 of the method for preparing the high-performance silicon-carbon negative electrode material of the present invention. DETAILED DESCRIPTION
[0024] Existing methods for preparing silicon-carbon anode materials still suffer from the problem of volume expansion and low conductivity during complete lithiation of silicon. The present invention proposes a method for preparing a high-performance silicon-carbon anode material, comprising the following steps: mixing nano-silicon, a polymer, and a solvent to form a spinning dope, electrospinning the dope to produce a polymer fiber membrane containing dispersed nano-silicon, and then carbonizing the dope at high temperature under a protective atmosphere to obtain the silicon-carbon anode material.
[0025] This invention aims to optimize the preparation process of high-performance silicon-carbon anode materials through electrospinning technology. The core concept is to first uniformly mix nanosilicon, polymer, and solvent to form a spinning precursor solution. Then, using the relatively convenient electrospinning process, a polymer fiber membrane containing nanosilicon is formed, resulting in a high specific surface area and nanoscale structure, which in turn improves the conductivity of the anode material. High-temperature carbonization treatment is performed under a protective gas environment to convert the polymer fiber membrane containing nano-silicon into a high-performance silicon-carbon negative electrode material. The role of the protective gas environment is to prevent the material from being oxidized at high temperature. The high-temperature carbonization treatment not only enhances the structural stability of the silicon-carbon negative electrode material, but also improves its electrical conductivity and lithium storage performance, making it a high-performance negative electrode material. At the same time, this process not only aims to solve the problem of volume expansion and low electrical conductivity of silicon during complete lithiation in the preparation method of silicon-carbon negative electrode materials in the existing technology, but also solves the problem of cumbersome process, opening up an innovative path that can ensure the excellent performance of the material and greatly simplify the production process. It has successfully prepared a silicon-carbon negative electrode material with excellent electrochemical properties, which not only has high capacity and long life, but also has a relatively simple preparation process and has the potential for industrial application.
[0026] Specifically, the preparation method of the high-performance silicon-carbon negative electrode material comprises the following steps: First, a polymer is dissolved in a solvent to form a polymer solution, wherein the mass ratio of the polymer to the solvent is (1:8) to (1:9); the polymer is one or more of polyethylene oxide, polycaprolactone, polyvinyl alcohol, polyvinyl pyrrolidone, polyvinylidene fluoride, polyacrylonitrile, polylactic acid, polyethersulfone, polyurethane, polystyrene, and polyamide; and the solvent is one or more of deionized water, ethanol, N,N-dimethylformamide, N,N-dimethylacetamide, chloroform, tetrahydrofuran, hexafluoroisopropanol, dichloromethane, acetone, and formic acid; Secondly, nano-silicon is added to the polymer solution and evenly dispersed to form a spinning solution; wherein the mass ratio of nano-silicon to polymer is (0.01-3):1; the particle size of nano-silicon is 10-800nm; Then, a polymer fiber membrane containing uniformly dispersed nano-silicon is obtained through an electrospinning process, wherein the spinning solution is introduced through a needle; the spinning solution is advanced at a rate of 0.01 to 0.8 mL / h, the inner diameter of the needle is 0.11 to 3.10 mm, the outer diameter of the needle is 0.25 to 3.50 mm, the roller receiving distance is 10 to 20 cm, the voltage is 12 to 28 kV, the temperature is 15 to 25°C, and the humidity is 20 to 50%. Finally, the polymer fiber membrane dispersed with nano-silicon is subjected to high-temperature carbonization under a protective atmosphere to obtain a silicon-carbon negative electrode material, wherein the high-temperature carbonization temperature is 300~700℃ and the time is 1~6h.
[0027] Preferably, in the electrospinning process, the receiving roller rotates at a speed of 300-500 r / min.
[0028] Preferably, the protective atmosphere is a nitrogen atmosphere or an argon atmosphere.
[0029] The implementation process of the present invention is described in detail below in conjunction with specific embodiments. However, it will be understood by those skilled in the art that the following embodiments are merely illustrative of the present invention and should not be construed as limiting the scope of the present invention. It should also be noted that, for ease of description, only the parts relevant to the invention are shown in the embodiments.
[0030] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application will be described in detail below with reference to the embodiments.
[0031] It should be noted that the endpoints of the ranges and any values disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoints of each range, the endpoints of each range and individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be considered to be specifically disclosed herein.
[0032] In the following examples, the particle size of nano-silicon in the raw materials used is 10-800 nm, and the remaining raw materials are common commercial products that can be directly purchased or can be prepared according to conventional techniques in the art.
[0033] 1. Specific embodiment of the method for preparing the high-performance silicon-carbon negative electrode material of the present invention Example 1 The method for preparing the high-performance silicon-carbon negative electrode material provided in this embodiment includes the following steps: First, polyethylene oxide is dissolved in deionized water to form a polymer solution; wherein the mass ratio of polyethylene oxide to deionized water is 1:9, and the CAS number of polyethylene oxide is 68441-17-8; Secondly, nano-silicon is added to the polymer solution and evenly dispersed to form a spinning solution; wherein the mass ratio of nano-silicon to polymer is 0.25:1; Then, a polymer fiber membrane containing uniformly dispersed nano-silicon was obtained through an electrospinning process. In the electrospinning process, the spinning solution was introduced through a needle. The propulsion rate of the spinning solution was 0.3 mL / h, the inner diameter of the needle was 0.11 mm, the outer diameter of the needle was 0.25 mm, the receiving roller distance was 15 cm, the voltage was 20 kV, the temperature was 15 ° C, the humidity was 20%, and the receiving roller speed was 350 rpm. Finally, the polymer fiber membrane dispersed with nano-silicon was carbonized at high temperature under an argon atmosphere to obtain a silicon-carbon negative electrode material. The high-temperature carbonization temperature was 450°C and the time was 60 min.
[0034] Example 2 The method for preparing the high-performance silicon-carbon negative electrode material provided in this embodiment includes the following steps: First, polyvinyl pyrrolidone is dissolved in a mixture of deionized water and ethanol to form a polymer solution; wherein the mass ratio of polyvinyl pyrrolidone to the mixture of deionized water and ethanol is 1:8, and the CAS number of polyvinyl pyrrolidone is 9003-39-8; Secondly, nano-silicon is added to the polymer solution and evenly dispersed to form a spinning solution; wherein the mass ratio of nano-silicon to polymer is 0.01:1; Then, a polymer fiber membrane containing uniformly dispersed nano-silicon was obtained through an electrospinning process. In the electrospinning process, the spinning solution was introduced through a needle; the spinning solution was advanced at a rate of 0.6 mL / h, the inner diameter of the needle was 1.65 mm, the outer diameter of the needle was 2.1 mm, the receiving roller distance was 10 cm, the voltage was 26 kV, the temperature was 15°C, the humidity was 20%, and the receiving roller speed was 500 rpm. Finally, the polymer fiber membrane dispersed with nano-silicon was carbonized at high temperature under a nitrogen atmosphere to obtain a silicon-carbon negative electrode material. The high-temperature carbonization temperature was 550°C and the time was 120 min.
[0035] Example 3 The method for preparing the high-performance silicon-carbon negative electrode material provided in this embodiment includes the following steps: First, polycaprolactone is dissolved in a mixture of dichloromethane and N,N-dimethylformamide to form a polymer solution; wherein the mass ratio of polycaprolactone to the mixture of dichloromethane and N,N-dimethylformamide is 1:8.5, and the CAS number of polycaprolactone is 24980-41-4; Secondly, nano-silicon is added to the polymer solution and evenly dispersed to form a spinning solution; wherein the mass ratio of nano-silicon to polymer is 0.25:1; Then, a polymer fiber membrane containing uniformly dispersed nano-silicon was obtained through an electrospinning process. In the electrospinning process, the spinning solution was introduced through a needle; the spinning solution was advanced at a rate of 0.3 mL / h, the inner diameter of the needle was 0.34 mm, the outer diameter of the needle was 0.64 mm, the receiving roller distance was 18 cm, the voltage was 22 kV, the temperature was 25°C, the humidity was 50%, and the receiving roller speed was 400 rpm. Finally, the polymer fiber membrane dispersed with nano-silicon was carbonized at high temperature under an argon atmosphere to obtain a silicon-carbon negative electrode material. The high-temperature carbonization temperature was 500°C and the time was 180 min.
[0036] Example 4 The method for preparing the high-performance silicon-carbon negative electrode material provided in this embodiment includes the following steps: First, polylactic acid is dissolved in dichloromethane to form a polymer solution; wherein the mass ratio of polylactic acid to dichloromethane is 1:9, and the CAS number of polylactic acid is 26100-51-6; Secondly, nano-silicon is added to the polymer solution and evenly dispersed to form a spinning solution; wherein the mass ratio of nano-silicon to polymer is 3:1; Then, a polymer fiber membrane containing uniformly dispersed nano-silicon was obtained through an electrospinning process. In the electrospinning process, the spinning solution was introduced through a needle; the spinning solution was advanced at a rate of 0.15 mL / h, the inner diameter of the needle was 3.10 mm, the outer diameter of the needle was 3.5 mm, the receiving roller distance was 20 cm, the voltage was 28 kV, the temperature was 20°C, the humidity was 25%, and the receiving roller speed was 500 rpm. Finally, the polymer fiber membrane dispersed with nano-silicon was carbonized at high temperature under a nitrogen atmosphere to obtain a silicon-carbon negative electrode material. The high-temperature carbonization temperature was 350°C and the time was 120 min.
[0037] Example 5 The method for preparing the high-performance silicon-carbon negative electrode material provided in this embodiment includes the following steps: First, polyurethane is dissolved in N,N-dimethylacetamide to form a polymer solution; wherein the mass ratio of polyurethane to N,N-dimethylacetamide is 1:9, and the CAS number of polyurethane is 51852-81-4; Secondly, nano-silicon is added to the polymer solution and evenly dispersed to form a spinning solution; wherein the mass ratio of nano-silicon to polymer is 0.5:1; Then, a polymer fiber membrane containing uniformly dispersed nano-silicon was obtained through an electrospinning process. In the electrospinning process, the spinning solution was introduced through a needle; the spinning solution was advanced at a rate of 0.4 mL / h, the inner diameter of the needle was 0.75 mm, the outer diameter of the needle was 1 mm, the receiving roller distance was 15 cm, the voltage was 16 kV, the temperature was 22°C, the humidity was 30%, and the receiving roller speed was 500 rpm. Finally, the polymer fiber membrane dispersed with nano-silicon was carbonized at high temperature under an argon atmosphere to obtain a silicon-carbon negative electrode material. The high-temperature carbonization temperature was 700°C and the time was 120 min.
[0038] Example 6 The method for preparing the high-performance silicon-carbon negative electrode material provided in this embodiment includes the following steps: First, polyacrylonitrile is dissolved in N,N-dimethylformamide to form a polymer solution; wherein the mass ratio of polyacrylonitrile to N,N-dimethylformamide is 1:8, and the CAS number of polyacrylonitrile is 25014-41-9; Secondly, nano-silicon is added to the polymer solution and evenly dispersed to form a spinning solution; wherein the mass ratio of nano-silicon to polymer is 0.6:1; Then, a polymer fiber membrane containing uniformly dispersed nano-silicon was obtained through an electrospinning process. In the electrospinning process, the spinning solution was introduced through a needle; the spinning solution was advanced at a rate of 0.2 mL / h, the inner diameter of the needle was 0.60 mm, the outer diameter of the needle was 0.90 mm, the receiving roller distance was 18 cm, the voltage was 24 kV, the temperature was 15°C, the humidity was 30%, and the receiving roller speed was 500 rpm. Finally, the polymer fiber membrane dispersed with nano-silicon was carbonized at high temperature under a nitrogen atmosphere to obtain a silicon-carbon negative electrode material, wherein the high-temperature carbonization temperature was 300°C and the time was 60 min.
[0039] In the present application, when the polymer is one or more of polyvinyl alcohol, polyvinylidene fluoride, polyethersulfone, polystyrene, and polyamide, the technical effects obtained are the same as those of the above embodiments.
[0040] In the present application, when the solvent is one or more of chloroform, tetrahydrofuran, hexafluoroisopropanol, acetone, and formic acid, the technical effects obtained are the same as those of the above embodiments.
[0041] 2. Experimental Examples Experimental Example 1 The morphology of the polymer fiber membrane dispersed with nano-silicon prepared in Example 1 was tested. Specifically, the morphology of the polymer fiber membrane dispersed with nano-silicon was characterized using a scanning electron microscope. The test results are as follows: Figure 1 As shown, it can be seen from the SEM image of the polymer fiber membrane dispersed with nano-silicon prepared in Example 1 that the polymer fibers with a diameter of about 1 μm are uniformly doped with silicon nanoparticles.
[0042] Experimental Example 2 The high performance silicon-carbon negative electrode material prepared in Example 2 was subjected to XRD testing, and the test results were as follows: Figure 2 As shown, it can be seen that the diffraction peak of the original elemental silicon is still retained in the silicon-carbon negative electrode material, indicating that no silicon oxide is produced.
[0043] Experimental Example 3 The high-performance silicon-carbon negative electrode materials prepared in Examples 1-6 were made into negative electrodes and assembled into lithium-ion batteries. The current density, capacitance, coulombic efficiency, and capacity retention after 100 charge and discharge cycles were tested. The battery performance was tested on a LAND battery performance tester. The specific test conditions were as follows: the battery was first left at rest for 24 hours at 25°C, and then the constant current charge and discharge test was started. During the test, the voltage range was precisely set at 0.01~3.0V (relative to Li / Li +), the lower limit is 0.01V to ensure that lithium ions are fully embedded in the silicon-carbon negative electrode material, and the upper limit is 3.0V to prevent overcharging from damaging the material structure. The current density is flexibly adjusted according to demand, ranging from 0.1 to 1A / g. Usually, a lower current density is selected when studying the first charge and discharge and long-term cycle performance. When testing the characteristics of high-rate charge and discharge, a higher current density, such as 1A / g, needs to be selected. Taking the current density of 0.1A / g as an example, the current density is set to 0.1A / g on the system, and charging begins. When the voltage reaches the upper limit of 3.0V, it is kept at rest for 10 seconds, and discharge begins until the voltage drops to 0.01V. It is kept at rest for 10 seconds, and the charge and discharge capacity after the first cycle is recorded, and the first coulombic efficiency is calculated; the cycle is repeated 100 times in the above manner, and the charge and discharge capacity and voltage curve changes are recorded in detail for each cycle. The charge and discharge capacity of the 100th cycle is recorded, and the capacity retention rate after 100 cycles is calculated; room temperature of 25°C is used as the basic test temperature. The specific test results are shown in Table 1: Table 1 Performance comparison of lithium-ion batteries corresponding to Examples 1-6
[0044] As can be seen from Table 1, the high-performance silicon-carbon negative electrode materials prepared by the preparation methods of the high-performance silicon-carbon negative electrode materials of Examples 1-6 are applied in lithium-ion batteries. Under the conditions of the corresponding current density, the first coulombic efficiency of the lithium-ion battery is above 89.2%, and can reach up to 99%; the capacity retention rate after 100 charge and discharge cycles is above 84%, and can reach up to 91%.
[0045] This shows that the high-performance silicon-carbon negative electrode material prepared by the preparation method of the high-performance silicon-carbon negative electrode material provided in the present application has high conductivity. Its application in lithium-ion batteries can significantly increase the capacity of the battery, improve the cycle stability and capacity retention rate of the lithium-ion battery, and extend its cycle service life.
[0046] The foregoing description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Those skilled in the art will readily appreciate that various modifications and variations are possible. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present invention are intended to be within the scope of protection of the present invention.
Claims
1. A method for preparing a high-performance silicon-carbon negative electrode material, characterized in that: The following steps are involved: After nano-silicon, polymer and solvent are mixed to form a spinning solution, an electrostatic spinning process is used to obtain a polymer fiber membrane dispersed with nano-silicon, which is then carbonized at high temperature under a protective atmosphere to obtain a silicon-carbon negative electrode material.
2. The method for preparing a high-performance silicon-carbon negative electrode material according to claim 1, characterized in that: The mass ratio of the nano silicon to the polymer is (0.01-3):1; the particle size of the nano silicon is 10-800 nm.
3. The method for preparing a high-performance silicon-carbon negative electrode material according to claim 1, characterized in that: The polymer is one or more of polyethylene oxide, polycaprolactone, polyvinyl alcohol, polyvinyl pyrrolidone, polyvinylidene fluoride, polyacrylonitrile, polylactic acid, polyether sulfone, polyurethane, polystyrene and polyamide.
4. The method for preparing a high-performance silicon-carbon negative electrode material according to claim 1, characterized in that: The solvent is one or more of deionized water, ethanol, N,N-dimethylformamide, N,N-dimethylacetamide, chloroform, tetrahydrofuran, hexafluoroisopropanol, dichloromethane, acetone, and formic acid.
5. The method for preparing a high-performance silicon-carbon negative electrode material according to claim 1, characterized in that: The temperature of the high temperature carbonization is 300-800° C., and the time is 1-6 hours.
6. The method for preparing a high-performance silicon-carbon negative electrode material according to claim 1, characterized in that: The mass ratio of the polymer to the solvent is (1:8) to (1:9).
7. The method for preparing a high-performance silicon-carbon negative electrode material according to claim 1, characterized in that: In the electrospinning process, the spinning solution enters from the needle; wherein, the propulsion rate of the spinning solution is 0.01~0.8mL / h, the inner diameter of the needle is 0.11~3.10mm, the outer diameter of the needle is 0.25~3.50mm, and the roller receiving distance is 10~20cm.
8. The method for preparing a high-performance silicon-carbon negative electrode material according to claim 7, characterized in that: In the electrospinning process, the voltage is 12-28 kV, the temperature is 15-25° C., and the humidity is 20-50%.
9. A high-performance silicon-carbon negative electrode material, characterized in that: The high-performance silicon-carbon negative electrode material is prepared by the preparation method of any one of claims 1 to 8.
10. A negative electrode plate, characterized in that: The negative electrode plate comprises a high-performance silicon-carbon negative electrode material prepared by the method for preparing a high-performance silicon-carbon negative electrode material as described in any one of claims 1 to 8 or a high-performance silicon-carbon negative electrode material as described in claim 9.
Citation Information
Patent Citations
Nano-silicon amorphous carbon composition lithium ion battery cathode material and preparation method therefor
CN101527357A
Anode material used for lithium ion battery and preparation methods thereof
CN102637875A
Silicon carbon composite negative electrode material and preparation method thereof
CN109713285A